Survival, growth and seed mass in a mixed tree species planting for Atlantic Forest restoration - Glaci Benvenuti-Ferreira; Jorge Schirmer; Osório A. Lucchese; Geraldo Ceni Coelho (AIMS Environmental Science, 2016)
Selection of tree species is a key aspect of restoration in megadiverse biomes such as the Atlantic Forest, especially in degraded areas with past intensive land use, which usually present severe limiting conditions. The species must have high survival and growth, not only in the transition between germination and seedling but also between seedling and adult plant until allowing the establishment of a self-sustaining and renewable community. In order to reach this goal, restoration initiatives carried out in the Atlantic Forest have employed high-diversity plantings of tree species from different successional guilds. Notwithstanding, long-term silvicultural knowledge is scarce for the native species from this biome, and the effectiveness of these models is controversial. Our investigation has compared the survival and growth of species and guilds in high-diversity tree species plantings in areas with previous agricultural intensive use. The species and guilds were also compared with respect to seed mass since this parameter is pointed out as an indicator of high survival in early stages. Pioneer and secondary species did not present differences in survival and seed mass, although pioneers exhibited greater growth rate. The late successional (LS) species had lower survival and growth, and higher seed mass. Survival after 8 months and between 8–15 months after seedling planting was inversely correlated with seed mass (r2 = 0.35 and r2 = 0.36, P < 0.001). On the other hand, survival after 8 months was correlated with relative growth rate (RGR) in the same periods of time (r2 = 0.34, P < 0.001). Overall average survival was 41% after 15 months, with the survival of LS species at an average of 12%. Data suggests that the inclusion of LS seedlings could impair the efficacy of restoration during early phases, at least in highly degraded areas. Equally, the inclusion of species with high seed mass should be considered with caution.